Diagnosing postpartum depression in a mother of developmentally delayed infant: a case report - Usta, Genco; Akpak, Yaşam Kemal; Yılmaz, Onat (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Postpartum depression is the most common clinical entity of childbirth. Although there are conflicting results about the influence of postpartum depression on the children, the consequences of the illness might extend to preschool age or further. Because physicians encounter mothers at the same time with the babies in the examination room, it might be of particular importance to have the knowledge of symptoms of maternal depression and pay attention to the mental and physical well-being of both the mother and the baby. In this article we would like to present an 18 month old child who presented with psychomotor retardation with a mother diagnosed as postpartum depression.